Decoupling Analysis of Bulgaria’s Agriculture - Nenova, Radka (Journal of Empirical Studies, 2016)
The article examines the possibility for applying a decoupling analysis to Bulgaria’s agriculture by analysing the relationships between its driving force and environmental pressures. The analysis methodology is adjusted for the purposes of the study. The empirical study covers the period from 1990 to 2012, during which the Republic of Bulgaria, as a party to the UN Framework Convention on Climate Change (UNFCCC), had to implement certain measures to reduce its greenhouse gas emissions. The results of the analysis show that during that period absolute decoupling prevailed in Bulgaria’s agricultural sector.